A time-motion study and patient satisfaction in the fever clinic of a Government Medical College and Hospital in India - Mahua Chowdhury; Sucharita Maji; Manas Patra; Amitabha Chattopadhyay (Asian Journal of Medical Sciences, 2024)
Background: During the recent pandemic, the number of patients with influenza-like symptoms had considerably increased in fever clinics of hospitals leading to queuing and increased patient dissatisfaction. Aims and Objectives: A time-motion study was therefore designed to evaluate the time taken at different service delivery points in the fever clinic and patient satisfaction regarding service delivery time. Materials and Methods: An institutional cross-sectional observational study was conducted at the fever clinic of Midnapore Medical College and Hospital for 1 month. A total of 200 patients were selected by systematic random sampling from the fever clinic outdoors and their movement was recorded and satisfaction assessed. Results: Most patients visited the clinic during the start of the week and in the first half of the day. The total mean time required from entry to exit was 9089 s±143.0. The maximum time was spent waiting time in the fever clinic entry queue followed by that at the pharmacy. The minimum time required was at the nursing table followed by a doctor’s consultation. The maximum meantime for movement between two stations was between station 5 (laboratory investigation station) and station 6 (pharmacy), that is, 1144 s±183.6. The majority of the study population was not satisfied with the time management in the fever clinic whereas only 18.0% of the participants were fully satisfied. Conclusion: Identifying the loopholes and formulating an effective time management strategy can help deliver better patient care as well as boost patient satisfaction.